Where will China's shale gas industry go? A scenario analysis of socio-technical transition. (November 2022) - Wei, Dong; Zhao, Yiqi; Liu, Hongyuan; Yang, Dongbo; Shi, Kai; Sun, Yuping
Abstract: The successful development of shale gas industry in China has a significant impact on China's energy consumption structure and the world energy market. Based on the socio-technical transition theory, this study defines the development of shale gas industry as the socio-technical system transition of natural gas driven by technological innovation and management innovation. From the multi-level perspective, this study systematically analyzes the co-evolution dynamics of multiple factors in the development of shale gas industry, and further proposes the socio-technical scenarios of shale gas industry development by using the socio-technical scenarios method. The results show that the shale gas industry generally has a relatively favorable development environment, but it also faces many challenges, such as lack of internal capacity and government support. And the "Government led development", "Diversified development", "Green development" and "High cost development" are the four potential development paths for China's shale gas industry. Highlights: The socio-technical transition dynamics of China's shale gas industry are analyzed. The development prospect of China's shale gas industry is uncertain. Different combinations of driving factors will lead to different development paths. Put forward four potential development paths for China's shale gas industry.